Business opportunities in Israel and Egypt education and human resources. - Kaur, Sharanjit. (2008)
Investors seeking business opportunities in a foreign country have to study very carefully both the macroenvironment and the microenvironment of the country before an assessment of the feasibility and profitability of the investment can be made. The business environment of a country is largely affected by the political, economic, technological and social environment. Equally important is the availability of qualified human resources. The quality of human resources is dependent on the educational and skill level of the workforce. Also, prevailing labour laws can either facilitate or hinder foreign investment.